Digital Transformation in Public Services: A Comparative Analysis of the Effectiveness of Single Window Service Policies in Various Regional Governments - Aries Purwanto; Muh Irfan Mukhlishin; Mulyaningsih Mulyaningsih; Ryan Teo (Journal of Social Science Utilizing Technology, 2026)
Background. Digital transformation in public services has become a critical component in improving government service delivery. One of the most significant innovations in this area is the implementation of Single Window Service (SWS) policies, which aim to streamline public service access by offering citizens a single point of contact for multiple government services. Despite the widespread adoption of SWS policies, their effectiveness varies across different regions, largely due to differences in technological infrastructure, governance structures, and regional support for digital initiatives. Purpose. This study seeks to provide a comparative analysis of the effectiveness of SWS policies in various regional governments, examining the factors that influence their success and identifying the key outcomes of these policies. Method. A mixed-methods approach is employed, combining qualitative interviews with government officials, surveys of citizens, and quantitative performance data to assess service efficiency, citizen satisfaction, and administrative burden reduction. Results. The results show that regions with stronger digital infrastructure and better organizational readiness exhibit higher levels of SWS success, while those with limited resources struggle to achieve similar outcomes Conclusion. The study concludes that the effectiveness of SWS policies is contingent not only on technological infrastructure but also on governance and organizational factors, providing valuable insights for improving digital public service delivery.